Cerebral Cortical Microvascular Rarefaction in Metabolic Syndrome is Dependent on Insulin Resistance and Loss of Nitric Oxide Bioavailability. (August 2015) - Chantler, Paul D.; Shrader, Carl D.; Tabone, Lawrence E.; d'Audiffret, Alexandre C.; Huseynova, Khumara; Brooks, Steven D.; Branyan, Kayla W.; Grogg, Kristin A.; Frisbee, Jefferson C.
Abstract Objective Chronic presentation of the MS is associated with an increased likelihood for stroke and poor stroke outcomes following occlusive cerebrovascular events. However, the physiological mechanisms contributing to compromised outcomes remain unclear, and the degree of cerebral cortical MVD may represent a central determinant of stroke outcomes. Methods This study used the OZR model of MS and clinically relevant, chronic interventions to determine the impact on cerebral cortical microvascular rarefaction via immunohistochemistry with a parallel determination of cerebrovascular function to identify putative mechanistic contributors. Results OZR exhibited a progressive rarefaction (to ~80% control MVD) of the cortical microvascular networks vs. lean Zucker rats. Chronic treatment with antihypertensive agents (captopril/hydralazine) had limited effectiveness in blunting rarefaction, although treatments improving glycemic control (metformin/rosiglitazone) were superior, maintaining ~94% control MVD. Chronic treatment with the antioxidant TEMPOL severely blunted rarefaction in OZR, although this ameliorative effect was prevented by concurrent NOS inhibition. Conclusions Further analyses revealed that the maintenance of glycemic control and vascular NO bioavailability were stronger predictors of cerebral cortical MVD in OZR than was prevention of hypertension, and this may have implications for chronic treatment of CVD risk under stroke‐prone conditions.